Isolation and Selection of Potential Isolates of Dark Septate Endophyte Fungi from Pinus merkusii Roots - Akhir, Jumadil; Budi, Sri Wilarso; Herliyana, Elis Nina; Surono (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2023)
Root isolation activities to obtain dark septate endophytic fungi are currently mostly carried out on agricultural and plantation crops, while less so on forestry crops. Roots are a suitable habitat for the growth of various microorganisms, including dark septate endophytic fungi. The research aims to isolate the roots of Pinus merkusii plants from four locations, test pathogenicity, and test the biomass of sweet caisim mustard seeds. The research used a descriptive method by observing the number of dark septate endophytic fungal isolates obtained and the pathogenicity of these isolates. Meanwhile, sweet ciasim mustard seed biomass from the pathogenicity test results of non-pathogenic isolates was analyzed using a completely randomized design. The results of root isolation from Pinus merkusii stands obtained as many as 25 isolates by isolating 1,160 root segments. Isolation of Pinus merkusii roots from the IPB Dramaga Campus obtained 16 isolates, Dabun Gelang Village, Gayo Lues Regency obtained 2 isolates, Gunung Walat University Forest obtained 2 isolates, and Gunung Halimun Salak National Park obtained 5 isolates. Pathogenicity tests showed that 12 isolates were pathogenic and 13 isolates were non-pathogenic. Biomass analysis of sweet ciasim mustard seeds on non-pathogenic isolates obtained the highest biomass in the control treatment (not inoculated) and the lowest in isolates Apg 23.5 and Hs 14.6b. There is still a lack of isolates obtained from isolation activities in this research, so it is necessary to find an appropriate sterilization method to obtain the maximum number of isolates and have the potential to become non-pathogenic isolates. Keywords: Pinus merkusii, dark septate endophyte, isolation